Training Science Teacher Understanding in Creating Science Learning Assessments Using the Quizalize Application - Mahdian Mahdian; Parham Sa'adi; Fauzia Dwi Sasmita; Yulia Fernandita; Misbah Misbah; Surya Hayati; Indah Noor Khasanah; Dhea Suntia; Amelia Karina (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Based on the questionnaire results filled out by the MGMP Natural Science teachers of Batola District, it was obtained that 44.44% stated they were sufficiently skilled in using technology when preparing science teaching materials, one of which is assessment. Therefore, the Mandatory Community Service Program team attempted to address the issue through training activities on creating technology-based science learning assessments using the Quizalize application. This training aims to enhance the knowledge and skills of MGMP Natural Science teachers in creating technology-based science learning assessments. The training will be conducted in 3 sessions hybridly, consisting of 1 session via Zoom on July 21, 2023, and 2 sessions in person at SMPN 2 Alalak School on July 29 & August 5, 2023. The methods used in this training consist of 4 stages, including planning, action, observation/evaluation, and reflection. Based on the evaluation questionnaire, it can be concluded that the participants understand and can create learning media by achieving a score of 75.08% and receiving positive responses.